2011
DOI: 10.1002/lt.22256
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological postconditioning protects against hepatic ischemia/reperfusion injury

Abstract: Postconditioning is a procedure based on the induction of intracellular protective reactions immediately after the onset of reperfusion. Because of the growing need to prevent ischemia/reperfusion (I/R) injury during liver surgery and transplantation, we investigated the possibility of pharmacologically inducing hepatic postconditioning. The effects of the adenosine A2A receptor agonist 2p-(2-carboxyethyl)-phenyl-amino-5 0 -N-ethylcarboxyamido-adenosine (CGS21680; 5 lmol/L) and the phosphatase and tensin homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 47 publications
(72 reference statements)
1
45
0
Order By: Relevance
“…Dal Ponte et al [8] also reported that pretreatment with a PI3K inhibitor prevented A2A receptor agonist-induced PostC of the liver. Previous studies showed that milrinone administration stimulated immediate accumulation of cAMP and elevation of PKA in the liver tissue, and pretreatment with a PKA inhibitor prevented milrinone-induced PreC [14,15].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Dal Ponte et al [8] also reported that pretreatment with a PI3K inhibitor prevented A2A receptor agonist-induced PostC of the liver. Previous studies showed that milrinone administration stimulated immediate accumulation of cAMP and elevation of PKA in the liver tissue, and pretreatment with a PKA inhibitor prevented milrinone-induced PreC [14,15].…”
Section: Discussionmentioning
confidence: 92%
“…Ischemia-and A2A receptor agonist-or ginsenoside Rb1-induced PostC markedly enhanced Akt phosphorylation of the liver tissues at reperfusion, and attenuated hepatic warm IR injury [6,8,22].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations